(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Thymomas are the common neoplasms of mediastinum, and type AB is the most frequent case. All thymomasare potential for invasion to adjacent tissues and considered malignant. Capsular invasion is one of itsprognostic indicators. Matrix metalloproteinase-2 (MMP-2) is a family of proteinases that has the abilityto degrade a component of extracellular matrix and affect tumor invasion and or metastasis. Cytoplasmicexpression of p21 protein can be significantly correlated with invasion and metastasis. The correlation of thesetwo proteins in thymoma has not been widely studied, hence we aimed to analyze the expression of MMP-2and p21 and investigate their correlation with capsular invasion of thymoma AB. This cross-sectional studywas performed on the 24 paraffin-embedded samples of thymomectomy during January 2013-Desember2019 at Anatomical Pathology Laboratory of Dr. Soetomo General Hospital Surabaya. The samples weredevided based on capsular invasion into 2 groups. Immunohistochemical staining was performed to detectexpression of p21 and MMP-2. The correlation was statistically analyzed using Spearman test. There wasno significant difference of MMP-2 expression between thymoma with capsular invasion and withoutcapsular invasion (p=0.839), and also no significant difference of p21 expression between thymoma withcapsular invasion and without capsular invasion (p=0.816). No correlation of MMP-2 and p21 expressionsin thymoma AB was revealed (p=0.255). In thymoma AB, the expression of MMP-2 and p21 were notcorrelate with capsular invasion. These results may contribute to the development of thymoma research.